KUALITAS TEKNIK RENANG GAYA BEBAS ATLET TIRTA KALUANG - Naluri Denay; Afrizal Afrizal; Argantos Argantos; M Iqbal Pratama; Wasti Danardani; Suci Nanda Sari (Riyadhoh : Jurnal Pendidikan Olahraga, 2022)
This study plans to decide the nature of the free-form swimming method. This examination is a sort of unmistakable exploration. The populace in this study were all swimming competitors from Tirta Kaluang Padang, adding up to 13 individuals. This testing was completed utilizing an all out inspecting method, which was 13 individuals. This examination instrument is through a free-form swimming strategy test. The information investigation strategy utilized recurrence circulation examination procedure with rate computation. The consequences of the review are, (1) The degree of evaluation for the nature of the body position procedure with an adequate level. (2) The degree of dominance of the nature of the arm procedure with an adequate level. (3) The degree of dominance of the nature of the foot development method with an adequate level. (4) The degree of dominance of the nature of breathing strategies with an adequate level. (5) The degree of dominance of the nature of coordination methods with an adequate level. Subsequently, the general examination results from 13 examples of swimming competitors from Tirta Kaluang Padang, acquired that the nature of free-form swimming procedures is in the adequate classification.